2011
DOI: 10.1002/ajmg.b.31212
|View full text |Cite
|
Sign up to set email alerts
|

Differential immune system DNA methylation and cytokine regulation in post‐traumatic stress disorder

Abstract: DNA methylation may mediate persistent changes in gene function following chronic stress. To examine this hypothesis, we evaluated African American subjects matched by age and sex, and stratified into four groups by post-traumatic stress disorder (PTSD) diagnosis and history of child abuse. Total Life Stress (TLS) was also assessed in all subjects. We evaluated DNA extracted from peripheral blood using the HumanMethylation27 BeadChip and analyzed both global and site-specific methylation. Methylation levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
277
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(289 citation statements)
references
References 60 publications
8
277
1
3
Order By: Relevance
“…To date, the hypothesis of a role for epigenetic mechanisms in PTSD and amygdala-dependent fear responses has only begun to be tested (Monsey et al, 2011;Roth et al, 2011;Smith et al, 2011). Thus, it is important to begin to assess the role of epigenetics in the amygdala and in PTSD, and the potential therapeutic efficacy of epigenetic drugs in alleviating PTSD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the hypothesis of a role for epigenetic mechanisms in PTSD and amygdala-dependent fear responses has only begun to be tested (Monsey et al, 2011;Roth et al, 2011;Smith et al, 2011). Thus, it is important to begin to assess the role of epigenetics in the amygdala and in PTSD, and the potential therapeutic efficacy of epigenetic drugs in alleviating PTSD.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have implicated epigenetic mechanisms in the psychopathology of PTSD. For example, Kerry Ressler's lab has shown that PTSD patients manifest altered DNA methylation in peripheral blood immune cells and identified several immune system-relevant genes that exhibit persisting epigenetic modification (Smith et al, 2011).…”
Section: Epigenetic Mechanisms In Ptsdmentioning
confidence: 99%
“…Parental separation in early childhood is also associated with increased CRP in adulthood (Lacey et al, 2013;McDade et al, 2013). Concentrations of IL-6, IL-1β, and TNF-α are elevated with childhood maltreatment (Gouin et al, 2012;Hartwell et al, 2013;Kiecolt-Glaser et al, 2011;Smith et al, 2011;Tietjen et al, 2012). Importantly, exposure to trauma in childhood is associated with increased risk for developing PTSD and other psychiatric conditions (Edwards et al, 2003).…”
Section: Ptsd and Inflammationmentioning
confidence: 99%
“…It has been clearly shown that maternal diet with supplementation in methyl donor changes gene expression in central nervous system and global DNA hypomethylation in prefrontal cortex [41]. Epigenetic regulation through DNA methylation or histone acetylation is essential factors in the control of psychiatric disorders such as depression and anxiety [42] [43]. Besides, methyl donors components are involved in some neurotransmitters synthesis namely dopamine, adrenaline, serotonin or acetylcholine known to be involved in regulation of depression state [44], as reported reduction of depression state of juveniles of dams fed to HFD and a methyl donors dietary.…”
Section: Discussionmentioning
confidence: 99%